1984
DOI: 10.1007/bf00231132
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of postural control to weightlessness

Abstract: Adaptation of motor control to weightlessness was studied during a 7-day spaceflight. The maintenance of control of upright posture was examined during a voluntary raising movement of the arm and during the voluntary raising on tiptoe. In order to evaluate the contribution of visual cues, three types of visual situations were examined: normal vision, central vision, and without vision. On the basis of cinematographic and mechanographic data, the postural perturbations consecutive to the movement of a body part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
82
1
3

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(98 citation statements)
references
References 11 publications
12
82
1
3
Order By: Relevance
“…It is possible that the signal-to-noise ratio originating from this length-tension relationship activated the compensatory mechanism in order to keep the signal-to-noise ratio rather constant or close to its reference value. As suggested by several authors (Clement, Gurfinkel, Lestienne, Lipshits, & Popov, 1984;Lestienne & Gurfinkel, 1988;Massion, 1992;Paillard, 1990), with experience, subjects elaborate an internal reference based in part on information originating from gravity forces. It is possible that subjects integrate such a reference, not (or not only) by means of specific receptors such as the otoliths, but also by means of the dynamic signals originating from the muscles activated during body oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the signal-to-noise ratio originating from this length-tension relationship activated the compensatory mechanism in order to keep the signal-to-noise ratio rather constant or close to its reference value. As suggested by several authors (Clement, Gurfinkel, Lestienne, Lipshits, & Popov, 1984;Lestienne & Gurfinkel, 1988;Massion, 1992;Paillard, 1990), with experience, subjects elaborate an internal reference based in part on information originating from gravity forces. It is possible that subjects integrate such a reference, not (or not only) by means of specific receptors such as the otoliths, but also by means of the dynamic signals originating from the muscles activated during body oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…Invariably, only the posterior muscles in the lower legs are activated to maintain quiet stance [1,18,19]. The relative positional relationship of body segments during this quiet stance is similar under conditions of weightlessness [7], suggesting that relatively stable mechanisms for posture maintenance exist. However, many previous studies have shown that remarkable individual variation exists regarding patterns of postural muscle activity in the trunk and thigh during quiet stance.…”
Section: Introductionmentioning
confidence: 99%
“…First, from animal studies, it is known that the load-related input, derived from proprioceptive and cutaneous afferents, can induce reflexes, some of which act directly on the central pattern generator (Conway et al 1987;Duysens and Pearson 1980;Gossard et al 1994;McCrea 1998;Pearson 1995;Pearson et al 1992;Whelan 1996). Proprioceptive influences, for example body loading and unloading, have strong facilitatory effects on the electromyographic activity (EMG) of extensor muscles such as the gastrocnemius (GM) and soleus (SO), but only marginal effect on the flexor muscles both in cats (Gossard et al 1994;Pearson et al 1998;Whelan et al 1995) and humans (Clement et al 1984;Dietz and Colombo 1998;Dietz et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions have been described for postural tasks. From earlier research on cats (Whelan 1996) and humans (Clement et al 1984;Dietz and Colombo 1998;Dietz et al 1992;Rossi and Decchi 1994), it has been shown that postural reflexes depend on body load. Interactions between body load and cutaneous reflexes in humans were investigated during standing (Rossi and Decchi 1994).…”
Section: Introductionmentioning
confidence: 99%